Crystallographic orientation dependent crack nucleation during the compression of a widmannstätten-structure α/β titanium alloy. (November 2018) - Yan, Zhibing; Wang, Ke; Zhou, Yu; Zhu, Xuefeng; Xin, Renlong; Liu, Qing
Abstract: Based on the observation on slip trace and crystallographic orientation, the corresponding slip system, Schmid factor (SF) and geometric compatibility parameter ( m' ) around the crack were calculated during compression of a widmannstätten-structure α/β titanium alloy. The difficult slip transfer, mainly occurring at a low m', induces a stress concentration on the grain boundary α (αGB ) and at the junction of several α colonies in the β grain, and then arouses a corresponding crack nucleation. The αGB -α colony boundary, α-β interface, colony-colony boundary and slip plane could act as the crack propagation ways according to the different crack nucleation site. Graphical abstract: Unlabelled Image